2005
DOI: 10.1042/bst20051502
|View full text |Cite
|
Sign up to set email alerts
|

Amazing grass: developmental genetics of maize domestication

Abstract: Crop plants were domesticated by prehistoric farmers through artificial selection to provide a means of feeding the human population. This article discusses the developmental genetics of crop domestication and improvement, including the historical framework and recent approaches in maize and other grasses. In many cases, selecting for a plant form that correlates with productivity involves controlling meristem activity. In the domestication of modern maize from its progenitor Zea mays ssp. parviglumis, QTL (qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 51 publications
(46 reference statements)
1
3
0
Order By: Relevance
“…In conclusion, the genetic relationships among Zea species were reported in many previous studies on the basis of morphological, cytogenetical, chemical, and molecular data [4]. The present work provided the first molecular evidence for systematic assessment of genetic relationship of Z. nicaraguensis in Zea species.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In conclusion, the genetic relationships among Zea species were reported in many previous studies on the basis of morphological, cytogenetical, chemical, and molecular data [4]. The present work provided the first molecular evidence for systematic assessment of genetic relationship of Z. nicaraguensis in Zea species.…”
Section: Discussionsupporting
confidence: 68%
“…In genus Zea , both wild taxa that have the common name “teosinte” and cultivated maize are diploid (n = 10) with the exception of tetraploid Z. perennis (n = 20). As the closest wild relative of maize, teosinte, which is indigenous to Mexico and Central America [4], is a potentially important resource for the study of maize genetics and evolution and for plant breeding.…”
Section: Introductionmentioning
confidence: 99%
“…Maize was domesticated in southern Mexico from wild teosinte grasses [10] and subsequently became absolutely dependent on humans to propagate [46]. Despite 9,000 years of divergent selection and breeding by indigenous peoples and modern breeders, we observed that maize seeds have maintained a shared set of associated bacteria with their wild ancestors and with one another.…”
Section: Discussionmentioning
confidence: 79%
“…They consist in measuring the genetic linkage between the mutated locus and a set of known polymorphic markers. The principle of genetic linkage, which requires the analysis of an offspring population generated from the mutant organism, has been established more than one century ago (Sturtevant, 1913 ) and was successfully used in developmental studies in animals and plants (Vollbrecht and Sigmon, 2005 ). It relies on the frequency of the recombination events (cross-overs) during the meiotic stage: the closest to the mutation one marker, the lowest the number of recombination between these two loci in the progeny (Figure 1 ).…”
Section: To Which Extent Can Current Forward Genetic Approaches Be Prmentioning
confidence: 99%